2018
DOI: 10.3324/haematol.2017.180059
|View full text |Cite
|
Sign up to set email alerts
|

Desmopressin in moderate hemophilia A patients: a treatment worth considering

Abstract: Desmopressin increases endogenous factor VIII levels in hemophilia A. Large inter-individual variation in the response to desmopressin is observed. Patients with a lower baseline factor VIII activity tend to show a reduced response, therefore, desmopressin is less frequently used in moderate hemophilia A patients (baseline factor VIII activity 1-5 international units/deciliter), even though factor VIII levels may rise substantially in some of them. We aim to describe the response to desmopressin in moderate he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
28
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 33 publications
1
28
1
Order By: Relevance
“…(5) Desmopressin raises vWF and FVIII levels, while anti-fibrinolytic agents inhibit fibrin clot degradation, and have all been shown to be useful in controlling haemophilic bleeding especially in patients with mild and moderate haemophilia. (31,32) Tranexamic acid in particular has been widely and successfully used alone or in combination with other antihaemophilic agents in the prevention and management of various haemophilic bleedings due to accidental or surgical trauma in haemophiliacs. (32) The only exception to the use of anti-fibrinolytic agents is urinary tract bleeding because of the possible risk of obstructive uropathy that may occur as a result of fibrin clot formation in the urinary tract.…”
Section: Discussionmentioning
confidence: 99%
“…(5) Desmopressin raises vWF and FVIII levels, while anti-fibrinolytic agents inhibit fibrin clot degradation, and have all been shown to be useful in controlling haemophilic bleeding especially in patients with mild and moderate haemophilia. (31,32) Tranexamic acid in particular has been widely and successfully used alone or in combination with other antihaemophilic agents in the prevention and management of various haemophilic bleedings due to accidental or surgical trauma in haemophiliacs. (32) The only exception to the use of anti-fibrinolytic agents is urinary tract bleeding because of the possible risk of obstructive uropathy that may occur as a result of fibrin clot formation in the urinary tract.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the lack of adequate use of pharmacological agents such as desmopressin and antifibrinolytic agents (epsilon amino caproic acid and tranexamic acid) was identified in a previous study as a major limitation in the management of haemophilia in tropical developing countries [8] . Desmopressin raises vWF and FVIII levels, while antifibrinolytic agents inhibit fibrin clot degradation; all have been shown to be useful in controlling haemophilic bleeding, especially in patients with mild and moderate haemophilia [36,37] . Tranexamic acid in particular has been widely and successfully used alone or in combination with other anti-haemophilic agents in the prevention and management of bleeding due to accidental or surgical trauma in haemophilia patients [37] .…”
Section: Discussionmentioning
confidence: 99%
“…Given that the RISE study demonstrated a partial/complete DDAVP response in 21% of patients with moderate hemophilia A, DDAVP should not be completely discarded from the therapeutic armamentarium for moderate hemophilia A, especially as an adjunct agent to reduce FVIII exposure. 16…”
Section: Discussionmentioning
confidence: 99%